Making a spectacle : examining curriculum/pedagogy as recovery from political trauma - Ruby, Megan; Angelo-Rocha, Michelle; Hickey, Mark; Agosto, Vonzell (Curriculum and pedagogy series., 2021)
"This book edition offers a collection of scholarship and reflections that goes beyond theoretical conversations. This volume opens the door for a dialog not only by scholars but also by educators, activists, and students who believe in inclusive and equal access to education for all individuals regardless of race, ethnicity, immigration status, gender, sexuality, religion, and other identities. In this volume, the authors examine curriculum and pedagogy as a tool for recovery from political trauma and healing. We used this as an opportunity to confront some of the politically shameful situations affecting educational environments, homes, neighborhoods, enclaves, and regions marked by socioeconomic inequality. We present wide-open questions: How are educators and school leaders learning to interact with one another, students, their families, and community while facing increased mass school shootings, police violence, racial profiling, unequal access to education and basic needs during a pandemic (COVID-19), and other forms of sociopolitical stress influenced by discrimination, institutional racism, and White nationalism? What curricular and pedagogical geographies are educators and students afforded through which to process their emotional responses to ecological or political activities witnessed in schools and their surrounding areas? These chapters and reflections/perspectives represent a diversity of positionalities within critical intersections of power and privilege as they relate to identity, culture, and curriculum and social justice, schools, and society"--